2020
DOI: 10.3389/fmicb.2020.00111
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Pressure Resistance in Escherichia coli Relates to Protein Folding and Aggregation

Abstract: The locus of heat resistance (LHR) confers extreme heat resistance in Escherichia coli. This study explored the role of the LHR in heat and pressure resistance of E. coli, as well as its relationship with protein folding and aggregation in vivo. The role of LHR was investigated in E. coli MG1655 and the pressure resistant E. coli LMM1010 expressing an ibpA-yfp fusion protein to visualize inclusion bodies by fluorescence microscopy. The expression of proteins by the LHR was determined by proteomic analysis; inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…S. enterica probably readily survived in dried egg powder that was a frequent source of outbreaks of salmonellosis in the 1940s. In this line, the TLPQC locus has recently also been shown to mediate pressure tolerance and tolerance against oxidizing agents used in the food industry (Li et al, 2020;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. enterica probably readily survived in dried egg powder that was a frequent source of outbreaks of salmonellosis in the 1940s. In this line, the TLPQC locus has recently also been shown to mediate pressure tolerance and tolerance against oxidizing agents used in the food industry (Li et al, 2020;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of plasmids toward genomic plasticity reaches beyond the provision of pathogenicity factors, antimicrobial resistance determinants, and degradation pathways (Koraimann, 2018;Pilla and Tang, 2018;Shintani et al, 2010). One plasmid-encoded feature is the up to 19 kbp long Transmissible Locus of Protein Quality Control (TLPQC) which mediates elevated tolerance against lethal temperature, pressure, and oxidatives (Boll et al, 2017;Lee et al, 2016;Li and Ganzle, 2016;Li et al, 2020;Wang et al, 2020). The TLPQC locus, originally derived from an environmental species, has also been obtained by clinically relevant bacteria (Bojer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that genetic strategies supporting the acquisition of pressure resistance include both loss and acquisition of some genes (Garcia-Hernandez, 2015; Hauben et al, 1997;Li et al, 2020;Vanlint et al, 2013). Resistance of pathogens to high pressure was described in wild-type strains or to laboratory-based selection and genetic modifications.…”
Section: Genetic Determinants Of Pressure Resistancementioning
confidence: 99%
“…However, the relationship between high pressure and protein aggregation is not very clear. Some studies showed that high pressure caused formation of cytosolic‐aggregated clumps corresponding to aggregation of cytoplasmic proteins and condensation of the nucleoid in both Gram‐positive and Gram‐negative bacteria (Kaletunc, Lee, Alpas, & Bozoglu, 2004; Mañas & Mackey, 2004; Mohamed, Diono, & Yousef, 2012), while other studies, which were based on microscopic observations with single cells that were labeled with fluorescent indicators of protein aggregation, demonstrated that high pressure dissociates intracellular protein aggregates (Govers & Aertsen, 2015; Govers, Dutre, & Aertsen, 2014; Li et al., 2020). High pressure induces intracellular oxidative stress through the increased oxidation of cytoplasmic disulfide bonds and the accumulation of the catalyst iron, which is induced by denaturation of proteins containing Fe‐S clusters in the cytoplasm (Aertsen et al., 2005; Gänzle & Liu, 2015).…”
Section: Cellular Alterations By High Pressure From Membrane To Cytopmentioning
confidence: 99%
See 1 more Smart Citation